2018
DOI: 10.3389/fnagi.2018.00023
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cognitive Training in Older Adults with and without Subjective Cognitive Decline Is Associated with Inhibition Efficiency and Working Memory Span, Not with Cognitive Reserve

Abstract: The present study explores the role of cognitive reserve, executive functions, and working memory (WM) span, as factors that might explain training outcomes in cognitive status. Eighty-one older adults voluntarily participated in the study, classified either as older adults with subjective cognitive decline or cognitively intact. Each participant underwent a neuropsychological assessment that was conducted both at baseline (entailing cognitive reserve, executive functions, WM span and depressive symptomatology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 35 publications
2
31
2
Order By: Relevance
“…In a study conducted by Bamidis et al (2015) with a community-dwelling sample of CI and cognitively impaired older adults, the authors reported a robust modulation (inverse) effect of executive functions’ baseline performance on training benefits in global cognition. Additionally, López-Higes et al (2018) have shown a compensation effect regarding general cognitive status in SCD participants with lower interference efficiency at the baseline. Following the administration of a task-switching intervention in three different populations (children, young, and older adults), Karbach et al (2017) demonstrated that this training program led to a reduction of age differences.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In a study conducted by Bamidis et al (2015) with a community-dwelling sample of CI and cognitively impaired older adults, the authors reported a robust modulation (inverse) effect of executive functions’ baseline performance on training benefits in global cognition. Additionally, López-Higes et al (2018) have shown a compensation effect regarding general cognitive status in SCD participants with lower interference efficiency at the baseline. Following the administration of a task-switching intervention in three different populations (children, young, and older adults), Karbach et al (2017) demonstrated that this training program led to a reduction of age differences.…”
Section: Introductionmentioning
confidence: 87%
“…If older adults with SCD have higher risk of developing dementia ( Jessen et al, 2014 ), it is of great interest to investigate benefits of CT in this population in comparison with CI participants, as well as to find which factors might be associated with greater gains subsequently. Considering a recent work where results evidenced that the UMAM CT program was most beneficial for SCD participants in explaining that their efficiency in inhibition support their general cognitive performance, while the Cis’ WM capacity was the most important performance predictor ( López-Higes et al, 2018 ), our hypothesis are as follows: (1) We expected that CR will not have a significant role as predictor of CT outcomes in language in any group; (2) We hypothesized that sentence comprehension and naming will be most improved in the SCD’s participants after the CT intervention than in those pertaining to the CI’s older group; (3) Provided that the UMAM program is multifactorial, we anticipate a positive effect on participants’ executive functioning which, in turn, will explain linguistic performance; Finally, we assume that program effects will be different depending on the group considered. In short, within the group of older adults with SCD a greater weight of inhibition is expected as a predictor/mediator of linguistic performance, while in the group of CI participants the variable with the greater weight will be a measure related to updating and monitoring representations in WM.…”
Section: Introductionmentioning
confidence: 99%
“…Previous training studies with OAs yielding data that speak to these two accounts have revealed mixed results, either supporting the compensation account (López-Higes et al, 2018;Roheger, Meyer, Kessler, & Kalbe, 2019;Witlock, McLaughlin, & Allaire, 2012;Zinke et al, 2014), the magnification account (Matysiak, Kroemeke, & Brzezicka, 2019), or both (depending on the type of transfer task: Borella et al, 2017). A recent study by Fu, Maes, Kessels, and Daselaar (2017) provided support for the magnification account.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, various types of complaints may have different meaning for the development of predictive subtypes of MCI or dementia (Gu, Fischer, Saposnik, & Schweizer, 2013). Regarding the importance of data in clinical practice, it has been shown that cognitive function training reduces the severity of SCD in healthy older adults (Kwok, Bai, Li, Ho, & Lee, 2013), especially in adults with SCD (López-Higes et al, 2018) and after stroke (van de Ven et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Referring to the discussions outlined in the introduction, whether the SCD can be considered as an indicator of actual cognitive difficulties or depressive mood, we have reason to indicate two mechanisms of SCD -emotional and/or cognitive. Stimulation of cognitive functions and/or prevention of depression (treatment) are effective in reducing complaints in people without dementia (Kwok et al, 2013;López-Higes et al, 2018;van de Ven et al, 2017). However, these techniques may not be effective when complaints are part of developing dementia.…”
Section: Discussionmentioning
confidence: 99%